Pengaruh Pemanfaatan Campuran Limbah Buah Durian dan Ampas Tahu Hasil Fermentasi dengan Pleurotus ostreatus dalam Ransum terhadap Performans Broiler - V. Y. Laoli; Nuraini Nuraini; Mirzah Mirzah (State Islamic University of Sultan Syarif Kasim Riau, 2020)
This study was conducted to determine the effect of fermented of Durian Waste and Tofu Waste (DWTW) mixture with Pleurotus ostreatus in rations on broiler performance. The material used in this study was 100 DOC broiler strain Arbor Acres (AA) CP-707. This study was designed using a completely randomized design consisting of 5 treatments and 4 replications in which each flock consisting of 5 chickens. The treatments were inclusion the levels of DWTW in rations, namely, 0, 6, 12, 18 and 24%. The observed variables included feed consumption, body weight gain, and feed conversion ratio. The results of this study indicated that the using of DWTW in broiler ration did not significant effect (P>0.05) on feed consumption, body weight gain and feed conversion ratio. In conclusion, DWTW can be utilized up to 24% in broiler rations. In this condition, average feed consumption, body weight gain, and feed conversion 57.34 g/chicken/day, 36.55 g/chicken/day and 1.57 respectively.